THE CHARACTERISTICS OF AROMATHERAPY CARRAGEENAN GEL FROM SEAWEED (Eucheuma cottonii) USING 5% KOH CONCENTRATION - Imam Kristof Octaviaman. H; Mery Sukmiwati; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT This study aims to determine the characteristics of aromatherapy carrageenan gel from seaweed (Eucheuma cottonii) using 5% KOH concentration immersion and without KOH immersion and also to find out which one is the best for making seaweed aromatherapy fragrance gel. The test used was the T-test with two types of treatment, namely without KOH immersion (control) (F1), and 5% KOH immersion (F2), with 3 replications so there were 6 experimental units. Parameters measured were organoleptic test (hedonic quality) in the form of smell test and visual test as well as chemical analysis in the form of viscosity test, ash and water content. This research was carried out at the Fishery Products Technology Laboratory, Food Chemistry Laboratory, Faculty of Fisheries and Marine Sciences, Riau University, Natural Mineral Materials Technology Laboratory Chemical Engineering, Faculty of Engineering, Riau University in October 2021. The results showed that the best treatment was using 5% KOH concentration which the higher viscosity value of 35.18 cP, the visual value of 8.19 and the aroma value of 8.4 with specifications that are dense, elastic and already resembles a gel, while aroma has a distinctive aromatherapy fragrance. Meanwhile, the higher water content was 28.39% and the ash content was 28.45% without KOH immersion. Keywords: carrageenan flour, aromatherapy, potassium hydroxide